Hubungan Antara Persepsi Tentang Kesehatan Lingkungan Sekolah Dan Sikap Terhadap Otoritas Guru Dengan Minat Belajar Siswa - Susanti, Dhanty, Taufik Kasturi, S.Psi., M.Si., Ph.D (2017)
The objectives of the study were to find out: 1) the relationship between perceptions about school environmental health and attitudes towards teacher authority with student learning interest; 2) The level of perception about school environmental health, attitudes towards teacher authority and student interest in learning; 3) Knowing the contribution of perception about school environment health and attitude of teacher authority to student learning interest. Hypothesis proposed Subyek research student of SMA Negeri I NogosariBoyolali Class X1; X3 and X5 totaling 116 students as many as 116 students. Data collection uses a scale of perception on school environmental health, teacher attitudes and student learning scores. The data analysis technique used regression analysis of two predictors. Based on the analysis results obtained correlation (R) = 0,598; P = 0,000 (p <0.01). Means there is a very significant relationship between the perception of school environmental health and attitudes towards the authority of teachers with student interest in learning. Correlation value (rx1y) = 0,500; Significance (p) = 0.000; (P <0.01) which means there is a very significant positive correlation between the perception about the health of school environment with student learning interest. Correlation value (rx2y) = 0.526; Significance (p) = 0,000 (p <0.01) means there is a very significant positive relationship between attitudes towards teacher authority with student learning interest. The result of research data analysis is known in general research have perception about school environment health attitude toward teacher authority and interest of student learning is classified.